Rhetoric Of Language In The Story Of Ashābul Kahfi According To Muhammad Thāhir Ibn Asyûr - Trisnani, Asif; Nalatama, Rahma; Lubis, Rahmat Hidayat (STIQ Amuntai, 2024)
The Qur'an is considered to contain many i'jaz sides which make it impossible for humans to create or imitate it. Of the many mufassir, not all of them discuss their interpretation with the style or aspect of language. This is where contemporary scholars and mufassir emergedThe name is Ibnu Ashur with his commentary Tahrir wa Tanwir, he is one of the interpreters who is very concerned about the various Ijaz and balaghoh aspects in the Al-Quran. And in the Qur'an there are many stories that are full of lesson and become life better, one of which is the story of the Ashabul-Kahf which is famous for its miraculous and full of grace, which is permissible for everyone to learn the lesson from this story with the secret meaning that come from Allah. style. The purpose of this study is to analyze hidden secrets that lie in the beauty of the choice of language, sentences, and arrangement of verses from the perspective of Al-Ijaz Al-Bayani in the story of Ashabul-Kahf according to Ibn Ashur. The method used by the researcher is a semantic analysis method which is part of linguistics which talks about the meaning of an expression or word in a language. Al-Bayani's dimension to the story of Ashabul-Kahfi lies in the beauty of the use of language. With the existence of sentences which are taraduf such as the sentences Rhasyada and Rasdhu, Kinayah is like the sentence dzarabna fii adzaniihim which means An-naum (sleep), and other examples.